Pengaruh Pelatihan Guru terhadap Kinerja Guru melalui Pengembangan Profesional Guru Madrasah Ibtidaiyah Se-Kota Batu - Rindra Risdiantoro (Institut Agama Islam Sunan Kalijogo Malang, 2021)
This study aims to 1) examin the effect of teacher training on improving the teachers performance of MI tecahers in Batu City through teachers professional development mediation, 2) explain the effect of training and professional development on the performance of MI teachers in Batu City, 3) explain the performance of MI teachers in Batu City. This research uses quantitative research approach with correlational causality type. The population are 215 MI teachers in Batu City, with a total sample of 65 teachers. Data collection instruments use questionnaire. Data analysis use Path Analysis. The result of this research are 1) there is a positive and significant effect of teacher training on improving the performance of MI teachers in Batu City through teachers professional development mediation, 2) training and professional development have a positive and significant effect on the teacher performance improvement of MI teachers in Batu City, 3) in high category of teachers performance of MI teacher in Batu City shows skilled teachers in teaching, skilled in management, discipline, regularity and good social relations.